070 Avoiding ANCAs becoming routine: the use of clinical guidelines for requesting anti-neutrophil cytoplasmic antibodies in neurology. Issue 3 (9th February 2012) - Hampton, J; Ward, R; Morgan, L; Miller, J A L
Abstract : Background: ANCA is highly specific for a group of small vessel vasculitides known as the ANCA associated small vessel vasculitides (AASVs). Consensus clinical guidelines have identified specific conditions where ANCA testing is appropriate to reduce unnecessary requests. For isolated neurological disorders this is restricted to peripheral neuropathy. The NUTH Neurology department has not previously followed any guidelines for ANCA testing and therefore requests could be for indications within or outside these guidelines. Aims: To determine whether requests for ANCA testing made by the Neurology department meet these guidelines for ANCA testing and whether if requests had been restricted to these criteria, this would have lead to any missed diagnoses of AASV. To use this audit to determine if the Neurology department should adopt the guidelines for ANCA testing. Methods: Analysis and comparison to the proposed guidelines of the indications for ANCA testing in: (1) 100 consecutive requests for ANCA testing from Neurology between September 2008 and October 2009. (2) All requests from Neurology between September 2003 and October 2009 that were ANCA positive. Results: 3135 requests for ANCA testing were made between September 2003 and October 2009. 48% of ANCA requests met the guidelines. Six of the eight ANCA positive results were requested for guideline meeting indications. An AASV was diagnosed in three of the ANCA positive patients. Conclusion: The proposed guidelines would have reduced the number of requests being made without missing any AASVs with an estimated annual saving of around £3500.